The Influence of Rewards on Games Flow, Challenge, and Its Effects Towards the Engagement of Malaysian Digital Traditional Games (Baghdad Science Journal, 2019)
Games engagement has become one of the main concerns in game industry. Early study revealed that Malaysian digital traditional games are suffering with the same issue due to several factors. One of it is the lack of the game itself. Although many Malaysian traditional games have been digitized, none of them has incorporated rewards despite its importance in games engagement. Realizing the importance of rewards in games engagement, one of Malaysian traditional Congkak has been chosen to be enhanced by incorporating rewards. Experiments have been conducted among 50 gamers among the Millennials. Prior interview, game demo and human test are conducted. Experiments focused on the influence of rewards on games flow, games challenge, and its effects which covers both positive and negative effects through four hypotheses. Findings show that three hypotheses are supported by the experiments thus suggested that rewards have significant influence on the measured constructs. The findings can be useful to new psychologists to obtain more understanding pertaining to games engagement through some experiments of rewards in traditional games. Ideas of incorporating rewards in digital traditional games can useful and beneficial to game developers in attracting gamer and make them hooked to the games.